Ayahuasca alters structural parameters of the rat aorta - Pitol, Dimitrius L. [UNESP]; Siéssere, Selma; Dos Santos, Rafael G.; Rosa, Maria L N M; Hallak, Jaime E C; Scalize, Priscilla H.; Pereira, Bruno F.; Iyomasa, Melina M.; Semprini, Marisa; Riba, Jordi; Regalo, Simone C H (Journal Of Cardiovascular Pharmacology, 2015)
Ayahuasca is a hallucinogenic brew traditionally used by Northwestern Amazonian indigenous groups for therapeutic purposes. It is prepared by the decoction of Banisteriopsis caapi with the leaves of Psychotria viridis. Banisteriopsis caapi contains β-carbolines that are inhibitors of monoamine oxidase and P. viris is rich in dimethyltryptamine, a 5-HT(1A/2A/2C) agonist. Acute ayahuasca administration produces moderate cardiovascular effects in healthy volunteers, but information regarding long-term use is lacking. This study investigated the effects of ayahuasca (2-4 mL/kg) in the rat aorta after acute and chronic (14 days) administration. Ayahuasca caused flattening and stretching of vascular smooth muscle cells and changes in the arrangement and distribution of collagen and elastic fibers. Chronic treatment with the higher dose significantly increased media thickness and the ratio of media thickness to lumen diameter. More research is needed on the cardiovascular function of long-term ayahuasca consumers.